Building a Legal Welfare State: Normative Analysis of Indonesia’s Economic Law Policies and Political Directions - Shafa, Nadia Farikha (Law and Judicial Review, 2025)
Objective: This article aims to analyze the concept of a legal welfare state in Indonesia by examining economic law policies and political directions, particularly those related to integrating the principles of social justice, environmental sustainability, and community economic empowerment under the rule of law. Research Design & Methods: This research is a normative legal study with a descriptive-analytical normative juridical approach that uses deductive analysis based on document studies and qualitative literature reviews of laws and regulations, policies, and academic literature to provide a comprehensive and systematic picture of the relevance of Indonesian economic legal policies within the framework of the idea of ​​a legal welfare state. Findings: The results of the study conclude that Indonesia's economic policy operates within a hybrid framework between market liberalization and state intervention, which requires institutional strengthening, integration of distributive justice and sustainability, and public participation as the main instruments for realizing policy legitimacy and reducing socio-economic inequality. Implications & Recommendations: The conclusion is that inclusive, participatory, and responsive economic legal policies, supported by strong law enforcement, regulatory harmonization, and consistent application of sustainability and social justice principles are essential to ensure legal certainty and sustainable national development. Contribution & Value Added: This article provides conceptual and practical contributions by enriching the discourse on the legal welfare state in Indonesia by examining economic legal policy and providing a normative basis for formulating fair, sustainable, and inclusive policies